ANALYSIS OF KENTUCKY CHICKEN PRODUCT QUALITY AND SERVICE ON CUSTOMER SATISFACTION USING VALIDITY TEST METHOD AND MULTIPLE LINEAR REGRESSION WITH SPSS - Harna Adianto; Lilik Martanto; Aswar Hanif; Endang Wahyudi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
In an era of increasingly intense market competition, factors such as price, taste, and attractive packaging have a positive influence on product quality and service, which in turn enhances customer satisfaction. Simultaneously, product quality and service significantly contribute to making Kentucky fried chicken products more appealing to the public. Therefore, it is necessary to examine improvements in chicken production quality as well as the availability of raw materials to meet consumer demand and generate income. This business is located in the Depok area. In its implementation, to support business planning, demand forecasting, and to reduce purchasing costs, an effective inventory system is essential. An inventory information system can also help increase sales, improve quality, and provide better service to customers. To ensure competitiveness in terms of taste, price, quality, and service, proper decision-making in purchasing raw materials is required. By applying with validity testing and multiple linear regression analysis (t-test) using SPSS, the final results aim to determine the relationship between product quality, service, and customer satisfaction, ensuring that specified needs are met